Accuracy of inter-hospital transfer information in Australian hospital administrative databases. (September 2019) - Assareh, Hassan; Achat, Helen M; Levesque, Jean-Frederic
Inter-hospital transfers improve care delivery for which sending and receiving hospitals both accountable for patient outcomes. We aim to measure accuracy in recorded patient transfer information (indication of transfer and hospital identifier) over 2 years across 121 acute hospitals in New South Wales, Australia. Accuracy rate for 127, 406 transfer-out separations was 87 per cent, with a low variability across hospitals (10% differences); it was 65 per cent for 151, 978 transfer-in admissions with a greater inter-hospital variation (36% differences). Accuracy rate varied by departure and arrival pathways; at receiving hospitals, it was lower for transfer-in admission via emergency department (incidence rate ratio = 0.52, 95% confidence interval: 0.51–0.53) versus direct admission. Transfer-out data were more accurate for transfers to smaller hospitals (incidence rate ratio = 1.06, 95% confidence interval: 1.03–1.08) or re-transfers (incidence rate ratio > 1.08). Incorporation of transfer data from sending and receiving hospitals at patient level in administrative datasets and standardisation of documentation across hospitals would enhance accuracy and support improved attribution of hospital performance measures.